CBSE Class 12-science Answered
Consider (sin2θ + cos2θ)2 = sin4θ + 2sin2θcos2θ + cos4θ
1 = sin4θ + 2sin2θcos2θ + cos4θ
1 = (1/x2) + 2/xy + (1/y2) ... (1)
z= 1/(1-sin2θcos2θ) = 1/(1-(1/xy))
1/xy = (z-1)/z
Put this in (1),
1 = (1/x2) + 2/xy + (1/y2)
1 = (1/x2) + 2(z-1)/z + (1/y2)
(1/x2) + (1/y2) = 1 - 2(z-1)/z
This video explains the properties of inverse trigonometric applications an...
Graphical representation of inverse trigonometric functions and principle ...
Understand the meaning of function to be continuous and discontinuous, comb...
Relationship between continuity and differentiability, concept of composite...
This video explains the concept of relations and types of relation like Emp...